2018
DOI: 10.1002/jctb.5784
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary economic assessment: a valuable tool to establish biocatalytic process feasibility with an in‐lab immobilized lipase

Abstract: BACKGROUND Despite the interest that commercial lipases arouse, the number of industrial applications is still very limited. Only high added value products such as cosmetic ingredients that can simultaneously benefit from ‘green chemistry’ and ‘natural’ labels of using biocatalysts can justify the final cost. In any case, process feasibility economic assessment in the first project stages must be done to take decisions about its industrial applicability. RESULTS This work presents an economic study of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 31 publications
3
17
0
1
Order By: Relevance
“…This decrease in activity cannot be attributed to a loss of biocatalyst during the recovery and washing processes or to any physical damage because it was collected after 11 uses, then its physical state was observed and its weight was checked (100% of the initial weight). The comparison of these results with previous operational studies carried out with Lipo-zyme® CALB L immobilized by adsorption to polystyrene resins (Lewatit® VP OC 1064 MD PH and Purolite® Lifetech™ ECR 1090 M) 19 shows that the immobilized lipase obtained in this research presents a higher operational stability than the other in-lab immobilized lipases tested as biocatalyst in the same reaction, which only allowed 7 and 5 uses, respectively.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This decrease in activity cannot be attributed to a loss of biocatalyst during the recovery and washing processes or to any physical damage because it was collected after 11 uses, then its physical state was observed and its weight was checked (100% of the initial weight). The comparison of these results with previous operational studies carried out with Lipo-zyme® CALB L immobilized by adsorption to polystyrene resins (Lewatit® VP OC 1064 MD PH and Purolite® Lifetech™ ECR 1090 M) 19 shows that the immobilized lipase obtained in this research presents a higher operational stability than the other in-lab immobilized lipases tested as biocatalyst in the same reaction, which only allowed 7 and 5 uses, respectively.…”
Section: Resultssupporting
confidence: 57%
“…[16][17][18] Attempts are also being made to obtain new immobilized lipase derivatives to reduce costs and to avoid total dependency on a trademark that could eventually withdraw the product from the market or increase its price. 19 In addition, this research have been complemented by economic and kinetic studies. [18][19][20] However, despite the excellent results obtained in these inquiries, further research efforts are needed before this knowledge can be implemented on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…293 The same groups reported that a cetyl ester mixture was obtained via esterification of myristic acid, palmitic acid or stearic acid (95%) and cetyl alcohol. 294 The reaction was catalyzed by different enzyme preparations, with N435 being the reference, and not overtaken by any of the new biocatalysts (with a product cost of 56.5 € per kg versus 58 € per kg for the best new catalyst). 287 In other cases, a transesterification reaction has been used to get the target product.…”
Section: Lewatit Vp Oc 1600mentioning
confidence: 99%
“…Once the unit costs for the biocatalyst, the substrates and the process equipment have been obtained, the calculations are carried out to obtain the cost per kilogram of EHMH product [33,34]. Table 5 displays, in the first row, the start-up time to reach the desired temperature and, in the second row, the reaction time until conversion remains constant.…”
Section: Materials and Equipment Cost Item Pricesmentioning
confidence: 99%